2019
DOI: 10.1002/pssa.201800612
|View full text |Cite
|
Sign up to set email alerts
|

In situ Photoluminescence Study of Plasma Effects on Passivation of Crystalline Silicon Coated with Aluminum Oxide

Abstract: A degradation of crystalline silicon surface passivation provided by aluminum oxide (Al2O3) is generally observed after plasma processes, e.g., deposition of amorphous silicon nitride. To minimize such detrimental effect, a better understanding of the interaction between plasma species and the Al2O3 layer is required. Using in situ photoluminescence, the passivation quality of as‐deposited and annealed crystalline silicon wafers coated with Al2O3 grown by atomic layer deposition is characterized in real time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…This negative impact could be related to UV emissions from the NH 3 + H 2 plasma. [ 21 ] In 1985, Jaeger and Hezel [ 22 ] showed that UV light with energy greater than 3.7 eV leads to the breaking of Si–H or Si–OH chemical bonds at the surface of the solar cell, which significantly degrades the passivation properties. This would be consistent with the larger degradation on (p) nc‐SiO x :H because of its higher transparency, thus letting more high‐energy photons reach the c‐Si/SiO x interface.…”
Section: Resultsmentioning
confidence: 99%
“…This negative impact could be related to UV emissions from the NH 3 + H 2 plasma. [ 21 ] In 1985, Jaeger and Hezel [ 22 ] showed that UV light with energy greater than 3.7 eV leads to the breaking of Si–H or Si–OH chemical bonds at the surface of the solar cell, which significantly degrades the passivation properties. This would be consistent with the larger degradation on (p) nc‐SiO x :H because of its higher transparency, thus letting more high‐energy photons reach the c‐Si/SiO x interface.…”
Section: Resultsmentioning
confidence: 99%
“…The setup developed in this study [15] is an evolution of an in situ photoluminescence (PL) system previously described by S. Abolmasov [16]. The PECVD reactor has a grounded electrode with a 9 mmdiameter hole in its center.…”
Section: In Situ Modulated Photoluminescence Pecvd Reactormentioning
confidence: 99%
“…1. Schematic representation of the in situ MPL acquisition setup coupled with a PECVD reactor [15]. At a given laser power output with a modulation depth of 6%, modulation frequencies ranging from 225 Hz to 625 Hz are used in order to measure various phase shifts and thus get a more reliable fitting for the value of the lifetime in equation (1).…”
Section: In Situ Modulated Photoluminescence Pecvd Reactormentioning
confidence: 99%
See 2 more Smart Citations